20 billion includes addiction and mental health, from HHS. Issue 39 (9th October 2020) - Knopf, Alison
Abstract : Providers are scrambling to get applications in for 20 billion in new grant money from the federal Department of Health and Human Services (HHS). The funding, announced Oct. 1, specifically includes organizations that provide mental health and addiction recovery treatment and services. It's an allocation under the third stimulus bill.